Pendampingan Pengurusan NIB UMKM Batik Wiroyudhan Melalui Online Single Submission Di Kelurahan Kepanjenlor - Nisa Hafi Idhoh Fitriana; Aida Hamiyatul Masturo; Amiral Haqiqi; Nafalia Mulyanatul Jannah; Ladisa Putri, Dinda Rhaima (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Business legality is crucial for it is the embodiment of Government's permission to carry out a business given to the businessmen. Besides, it has the role as a sign that the business is worthy, relevany, and able to gain more profit. This community service consists of three steps. It began with FGD involving UMKM batik wirotudhan as the partner. Partner selection is based on group of kknt 26's observation. Next, we did a survey to the Tax Office of Blitar to gather any relevant information related to the registration of Business Identification Number, including the procedures. In the end, we organize the registration of Business Identification Number online by OSS.